2017
DOI: 10.1017/ice.2017.131
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infections After Liver Transplantation: Prospective Surveillance and Evaluation of 250 Transplant Recipients in Canada

Abstract: OBJECTIVE To evaluate the incidence of surgical-site infections (SSIs) in a cohort of liver transplant recipients and to assess risk factors predisposing patients to these infections. DESIGN Prospective observational cohort study. SETTING Single transplant center in Canada. PATIENTS Patients who underwent liver transplantation between February 2011 and August 2014. METHODS Multivariate logistic regression was used to identify independent risk factors for SSIs in liver transplant patients. RESULTS We enrolled 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 23 publications
1
18
1
3
Order By: Relevance
“…Incidence of reoperation ranges between 6% and 22.7%, and it was shown that reoperation is associated with SSI. Linuma et al showed in their study following living donor liver transplantation that reoperation is an independent risk factor for SSI. In our study, incidence of reoperation was 28.7%, including three retransplantation procedures, which is higher than the figures reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Incidence of reoperation ranges between 6% and 22.7%, and it was shown that reoperation is associated with SSI. Linuma et al showed in their study following living donor liver transplantation that reoperation is an independent risk factor for SSI. In our study, incidence of reoperation was 28.7%, including three retransplantation procedures, which is higher than the figures reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the incidence of SSI secondary to biliary tract infections did not change depending on whether the type of anastomosis was duct‐to‐duct or Roux‐en‐Y hepaticojejunostomy . Yamamoto et al and Hollenbeak et al found that Roux‐en‐Y biliary reconstruction was an independent risk factor for SSI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(3,14) En cuanto a los agentes etiológicos, estos pueden ser virales, bacterianos, parasitarios y fúngicos (12). Las infecciones de espacio-órgano son el tipo más común de infecciones de sitio quirúrgico postoperatorias que se observan en receptores de trasplante hepático, y se menciona que su riesgo aumenta por la anastomosis de conducto a conducto y hemodiálisis antes del trasplante (9).…”
Section: -Neoplásicasunclassified